2012
DOI: 10.1007/s12011-012-9406-9
|View full text |Cite
|
Sign up to set email alerts
|

Nickel and Ultraviolet-B Stresses Induce Differential Growth and Photosynthetic Responses in Pisum sativum L. Seedlings

Abstract: Enhanced level of UV-B radiation and heavy metals in irrigated soils due to anthropogenic activities are deteriorating the environmental conditions necessary for growth and development of plants. The present study was undertaken to study the individual and interactive effects of heavy metal nickel (NiCl(2)·6H(2)O; 0.01, 0.1, 1.0 mM) and UV-B exposure (0.4 W m(-2); 45 min corresponds to 1.08 KJ m(-2)) on growth performance and photosynthetic activity of pea (Pisum sativum L.) seedlings. Ni treatment at high dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 46 publications
6
26
0
1
Order By: Relevance
“…1) and it appears that increased activity of SOD even could not bring down the level of ROS. Similar results were also observed in pea plants when exposed with Ni stress (Srivastava et al, 2012 (Shigeoka et al, 2002), whereas DHAR helps in the regeneration of ascorbate from dehydroascorbate by utilizing glutathione a non-enzymatic antioxidant. Another H 2 O 2 splitting enzymes CAT and POD that are heme containing tetrameric proteins.…”
Section: Activities Of Antioxidative Enzymessupporting
confidence: 79%
See 1 more Smart Citation
“…1) and it appears that increased activity of SOD even could not bring down the level of ROS. Similar results were also observed in pea plants when exposed with Ni stress (Srivastava et al, 2012 (Shigeoka et al, 2002), whereas DHAR helps in the regeneration of ascorbate from dehydroascorbate by utilizing glutathione a non-enzymatic antioxidant. Another H 2 O 2 splitting enzymes CAT and POD that are heme containing tetrameric proteins.…”
Section: Activities Of Antioxidative Enzymessupporting
confidence: 79%
“…2). At this treatment the elevated concentration of Ni in tissues might have caused interruption in the electron flow at various sites of photosynthetic electron transport chain as reported in earlier studies (Prasad et al, 2005;Srivastava et al, 2012) hence Ni is considered as the prime cause for ROS generation in plants under stress (Prasad et al, 2005;Gill and Tuteja, 2010). Compared to plants exposed to Ni under non-amended condition, the decrease in SOR content was 24, 27, 34 and 33%, and in H 2 O 2 content it was 9, 23, 36 and 34% at 100, 200 500 and 1000 mg DAP kg À 1 soil doses of phosphate amendment, respectively (Fig.…”
Section: Reactive Oxygen Species and Index Of Oxidative Damagesupporting
confidence: 58%
“…In this way, previous reports have shown that mutants impaired in the function of the ABA and ROS-regulated protein phosphates 2C (PP2Cs) ( abi-1 ) were sensitive to the combined impact of drought and heat, as well as salinity and heat (Suzuki et al, 2016; Zandalinas et al, 2016a). Furthermore, several studies have reported that the expression of different ROS-scavenging enzymes and the accumulation of different antioxidants exhibit a unique mechanism of response during stress combination that is different than that found in response to each individual stress (Rizhsky et al, 2002, 2004; Srivastava et al, 2012; Prasch and Sonnewald, 2013; Rivero et al, 2013; Pandey et al, 2015; Jin et al, 2016). …”
Section: Introductionmentioning
confidence: 98%
“…Studies indicate that UV radiation affects mainly photosystem II [33], and the main plant protection mechanism for that stress is the biosynthesis of UV-absorbing compounds, as phenolic compounds and flavonoids, that attenuate the penetration of the UV-B range of the solar spectrum through the leaf [32]. Among the negative effects of UV radiation on plants are reduced growth, reproduction, development, photosynthesis, and productivity [1,15,34]; but the effects vary among species. In the present study, UV radiation had a significant inhibitory effect on shoot length and fresh and dry weights of plants, and this agrees with the results from other studies [30,31] in which T. aestivum and other Brassica species were negatively affected in their growth by UV radiation.…”
Section: Single Exposurementioning
confidence: 99%
“…Studies have reported effects of high UV-B radiation on the physiology, growth and development of plants, which have also been modified by the presence of heavy metals [3,[12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%